2005
DOI: 10.1007/s10334-005-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fMRI acoustic noise on non-auditory working memory task: comparison between continuous and pulsed sound emitting EPI

Abstract: Conventional blood oxygenation level-dependent (BOLD) based functional magnetic resonance imaging (fMRI) is accompanied by substantial acoustic gradient noise. This noise can influence the performance as well as neuronal activations. Conventional fMRI typically has a pulsed noise component, which is a particularly efficient auditory stimulus. We investigated whether the elimination of this pulsed noise component in a recent modification of continuous-sound fMRI modifies neuronal activations in a cognitively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…9159], who argued that ''the addition of noise introduced an extra cognitive-perception demand (i.e., signal-to-noise extraction)'', which accounts for insular activation. Furthermore, a recent fMRI study demonstrated insula activity in more distractive conventional fMRI relative to a less disruptive scanning protocol [Haller et al, 2005]. A similar scenario can be found in the context of our study: since enhanced effort was necessary in the noisy scanning environment to retrieve intelligible information from the auditory stimuli, it is plausible that this particular region was significantly more engaged during continuous scanning.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…9159], who argued that ''the addition of noise introduced an extra cognitive-perception demand (i.e., signal-to-noise extraction)'', which accounts for insular activation. Furthermore, a recent fMRI study demonstrated insula activity in more distractive conventional fMRI relative to a less disruptive scanning protocol [Haller et al, 2005]. A similar scenario can be found in the context of our study: since enhanced effort was necessary in the noisy scanning environment to retrieve intelligible information from the auditory stimuli, it is plausible that this particular region was significantly more engaged during continuous scanning.…”
Section: Discussionsupporting
confidence: 87%
“…However, customary functional magnetic resonance imaging (fMRI) is hampered by acoustic noise produced during operation of the MR system, which affects the experimental integrity of auditory fMRI studies [Amaro et al, 2002;Haller et al, 2005;McJury and Shellock, 2000;Moelker and Pattynama, 2003]. In particuConny Schmidt and Tino Zaehle equally contributed to this work.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, for working memory tasks, we and others showed that increases in activation in the PFC and occipital cortices due to higher AN (Haller S et al, 2005;Tomasi D et al, 2005;) differed between men and women (Tomasi D et al, 2005).…”
Section: Introductionmentioning
confidence: 75%
“…The right middle frontal gyrus, located in the ventral and frontal pole area, is believed to reflect the coordination and shifting of information among multiple cognitive tasks and functions as an important area for executing and regulating working memory [33], [35]. Similarly, the detection of activation in both the lingual and fusiform areas located in the medial occipital cortex distinguished tasks involving different levels of working memory, suggesting that the solving of complex tasks can be attributed to these brain regions [36]. Our finding that acute exercise is associated with these brain regions is consistent not only with our hypothesis but also with recent studies using functional near-infrared spectroscopy (NIRS) [37], [38].…”
Section: Discussionmentioning
confidence: 99%